Molecular identification and distribution profile of Candida species isolated from Iranian patients. (August 2013) - Mohammadi, Rasoul; Mirhendi, Hossein; Rezaei-Matehkolaei, Ali; Ghahri, Mohammad; Shidfar, Mohammad Reza; Jalalizand, Nilufar; Makimura, Koichi
Abstract A total of 855 yeast strains isolated from different clinical specimens, mainly nail (42%) and vulva-vagina (25%) were identified by a set of polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP). Genomic DNA was extracted from fresh colonies using Whatman FTA Card technology. PCR assays were performed on the complete ribosomal DNA internal transcribed spacer (rDNA-ITS) region for all isolates and species identification was carried out through their specific electrophoretic profiles after digestion with the enzyme MspI. Those isolates suspected as Candida parapsilosis group were then subjected to amplification of the secondary alcohol dehydrogenase (SADH) gene and restriction digestion with NlaIII enzyme. In total, 71.1% of the strains were obtained from females and 28.9% from males. The age group of 31–40 years consisted of the highest frequency of patients with candidiasis. Candida albicans was the predominant species (58.6%) followed by C. parapsilosis (11.0%), C. glabrata (8.3%), C. tropicalis (7.0%), C. kefyr (5.8%), C. krusei (4.4%), C. orthopsilosis (2.1%), and C. guilliermondii (0.6%). A few strains of C. lusitaniae, C. rugosa, C. intermedia, C. inconspicua, C. neoformans and S. cerevisiae were isolated. We could not identify 8 (0.9%) isolates. Candida albicans remains the most frequently species isolated from Iranian patients; however, the number of non-C. albicans Candida species looks to be increasing. The simple and reliable PCR-RFLP system used in the study has the potential to identify most clinically isolated yeasts.